2007
DOI: 10.1097/01.mlr.0000252162.78915.62
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hospital Size and Teaching Status on Patient Experiences With Hospital Care

Abstract: The effect of hospital category on patient experiences with hospital care was small. Hospital category was not a major determinant of patient experiences during hospitalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
48
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 32 publications
12
48
2
Order By: Relevance
“…Low betweenhospital variation is a common finding in health services research [18,39]. Nevertheless, Selby et al [44] have shown that despite low ICCs for facilities, quality improvement efforts at the facility level lead to clinically significant improvements.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Low betweenhospital variation is a common finding in health services research [18,39]. Nevertheless, Selby et al [44] have shown that despite low ICCs for facilities, quality improvement efforts at the facility level lead to clinically significant improvements.…”
Section: Discussionmentioning
confidence: 98%
“…The hospital-level data were supplemented with data on two hospital structural characteristics, which in many studies have proven to explain differences in outcomes of care [18,19,36]. First, as a caseload indicator, we included data on the number of surgeries performed in each hospital on newly diagnosed breast cancer patients over the previous year (dichotomized by median split).…”
Section: Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…multiple attempts at injection) [19]. Second, the perceived higher priority given to training in teaching hospitals may be translated by some patients as poor quality of care [16][17][18]. We conclude:…”
Section: Intrapersonal Appraisalsmentioning
confidence: 97%
“…These studies suggest that altruistic motives apply to patient considerations to participate in clinical training [2,14,15]. But a significant number of students as well as preceptors still find that patients refuse to participate [11] because they associate clinical training with limited patient-physician continuity and increased discomfort during diagnosis and treatment [14,[16][17][18][19]. Pinnock et al [2] report that fear of emotional distress or pain can lead patients to refuse and clinical training may evoke feelings of anxiety among patients.…”
Section: Introductionmentioning
confidence: 97%